The Dominant Factors Related to the Breast Self-Examination Behavior of Female Students of SMAN 1 Asembagus - Daniar Faradina; Ainul Hidayati, S.Kep., Ns., M.KM; Umi Sukowati, S.Kep., Ns., M.Kep., Sp.Mat (PROFESSIONAL HEALTH JOURNAL, 2026)
Introduction: The incidence of breast cancer in Indonesia in 2020 showed 68,858 new cases, which contributed 16.6% of the total 396,914 new cancer cases overall. The WHO recommends cancer prevention as an essential component of all cancer control plans. Early detection through breast self-examination (BSE) is one of the recommended methods to reduce breast cancer mortality. However, awareness and practice of BSE among Indonesian women remain low. Several determinants of breast self-examination behavior have been identified, including family history, knowledge, attitudes, and family support. The purpose of this study is to analyze the dominant factors related to BSE behavior in female students at SMAN 1 Asembagus. Methods: This study used a cross-sectional method with a sample of 62 respondents drawn using a stratified sampling technique. The instrument used was a questionnaire. Data analysis used the chi-square test and multiple logistic regression. Results: Family history, knowledge, attitude and family support were proven to have a statistical relationship with the self-examination behavior of female students of SMAN 1 Asembagus with p values of 0.002; 0.000; 0.000; 0.044. The results of the multivariate test showed that family support was the dominant factor with an OR of 6.7 times the risk of performing self-examination. Conclusions: Family history, knowledge, attitude, and family support factors have a statistically significant relationship with BSE behavior in female students of SMAN 1 Asembagus. The dominant factor related to BSE behavior in female students of SMAN 1 Asembagus is the family support factor with the largest OR among other factors, namely 6.7. Nurses as health workers have a strategic role in educating and empowering families to provide optimal support, both emotionally, instrumentally, in terms of information, and through assessment. Keywords: Breast Cancer, BSE, Family History, Knowledge, Attitude, Family Support